Evaluasi Website Pemerintah Kota Jambi Menggunakan System Usability Scale - Pratama Azani Akbar (Prodi Sistem Informasi FST Universitas Jambi, 2021)
The Jambi City website or commonly called SIKOJA is a website created by the Jambi City Communications and Information Office (DISKOMINFO), the website presents the latest information in Jambi City. To produce a website that can present information effectively and efficiently, it is necessary to evaluate the website from the views of the website users themselves. One way to evaluate a website is to measure its usability level. This research was conducted to determine the level of website usability by using the System Usability Scale. System Usability Scale (SUS) is a usability method that can be used as an evaluation tool to see the level of usability of a website. System Usability Scale was introduced by John Brooke in 1986, testing using SUS involves end users in testing. The results of the assessment of the SUS questionnaire in the form of a SUS score which is also in the form of NPS (Net Promoter Score), acceptable, adjective, and the grade of the usability website that has been evaluated. SUS can be used for various types of products and services, including hardware, software, mobile devices, websites and applications. By distributing the System Usability Scale questionnaire, the results of the evaluation of the Jambi City Government website obtained a usability level with the SUS score obtained was 70.8 with a 56% percentile rating and above the average of the SUS Score in general, then for the grade, the City Government website Jambi is in grade, while on the adjectives scale the use of the Jambi city government's website is OK/enough, which means the website is feasible to use and the menus on the website function properly, but still need improvement, for marginal acceptability, for the NPS classification (promoters and detractors), are classified as passive. Respondents in this study are known to be passive towards the Jambi City Government website. This can be due to a lack of knowledge about the websites visited and also the website content which can be said to be incomplete.